A Morphological Analysis of Reactive Astrocytes in Alzheimer’s Disease: Therapeutic Implications of M1 Muscarinic Acetylcholine Receptor Modulation - Cregan, Allie (Université d'Ottawa | University of Ottawa, 2025)
Alzheimer’s Disease (AD) is the most common form of dementia, disproportionally affecting females, who account for nearly 60% of diagnoses. In AD, beta-amyloid (Aβ) accumulation triggers neuroinflammation driven by neuroglia, exacerbating disease progression. Reactive astrocytes play a critical role in AD pathophysiology, yet their morphological changes remain poorly characterized. Our lab previously demonstrated that VU0486846, an orally available positive allosteric modulator (PAM) of the M1 muscarinic acetylcholine receptors (M1 mAChRs), enhances cognitive function, reduces Aβ pathology, and decreases astrocyte and microglial activation in the hippocampus of female APPswe/PSEN1ΔE9 (APPswe) mice. However, its effects on astrocyte morphology remain unclear. Using optimized immunofluorescence staining and 3D reconstruction techniques, this thesis assessed astrocyte morphology in female APPswe and wildtype mice. Astrocytes in the hippocampus and cortex of APPswe mice showed hallmark features of reactive astrogliosis, including hypertrophic somas and processes, elongated processes, and increased branching complexity. Chronic treatment with VU0486846 for eight weeks, beginning at 6-months old, significantly reduced astrocyte soma volume, process volume, process length, and branching complexity in APPswe mice, restoring astrocyte morphology to wildtype levels. These findings suggest that VU0486846 mitigates astrocyte reactivity, potentially reducing neuroinflammation and supporting neuronal health in AD. This thesis reveals a novel mechanism by which M1 mAChR PAMs exert disease-modifying effects, highlighting their ability to reduce astrocyte reactivity and emphasizing their potential as therapeutic agents for AD, particularly in females.
Keywords: Astrocyte; Neuroinflammation; Reactive astrocyte; Morphology; M1 mAChR; Postive allosteric modulator; Alzheimer's disease; Positive allosteric modulator